Emergency Exemption Pesticide Registrations - Frederick M. Fishel (EDIS)
PI-132, a 3-page fact sheet by Frederick M. Fishel, describes a unique type of pesticide registration Â– Emergency Exemption, also known as a Section 18 registration, and examples of situations where it is warranted. Published by the UF Pesticide Information Office, August 2006.